2022
DOI: 10.1101/2022.09.23.509254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell type specific transcriptomic differences in depression show similar patterns between males and females but implicate distinct cell types and genes

Abstract: Major depressive disorder (MDD) is a common, heterogenous, and potentially serious psychiatric illness. Diverse brain cell types have been implicated in MDD etiology. Significant sexual differences exist in MDD clinical presentation and outcome, and recent evidence suggests different molecular bases for male and female MDD. We evaluated over 160,000 nuclei from 71 female and male donors, leveraging new and pre-existing single-nucleus RNA-sequencing data from the dorsolateral prefrontal cortex. Cell type specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 100 publications
(107 reference statements)
1
23
1
Order By: Relevance
“…Our DE analysis indicates that interneurons, especially PVALB, followed by SST and VIP, appear most altered in psychiatric disorders. This is in contrast to the preponderance of DE genes among excitatory neurons (relative to inhibitory) reported by recent single-nucleus studies of psychiatric disorders (29)(30)(31)(32)(33)(34), which might be influenced by higher sampling of excitatory neurons (Supplementary Figure 7). In our study, few DE genes were found overall in PYR cells.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Our DE analysis indicates that interneurons, especially PVALB, followed by SST and VIP, appear most altered in psychiatric disorders. This is in contrast to the preponderance of DE genes among excitatory neurons (relative to inhibitory) reported by recent single-nucleus studies of psychiatric disorders (29)(30)(31)(32)(33)(34), which might be influenced by higher sampling of excitatory neurons (Supplementary Figure 7). In our study, few DE genes were found overall in PYR cells.…”
Section: Discussioncontrasting
confidence: 95%
“…NPAS3 plays a broad role in neurogenesis, and mutations in this gene have been associated with SCZ and neurodevelopmental disorders (59,60). LCM-seq cell-specific disease signatures were also moderately consistent with those surveyed in recent human snRNA-seq datasets from MDD and SCZ (30,34), as assessed by rank-rank hypergeometric overlap analysis ( Supplemental Figure 4 , see Methods).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations